Cannabis use in early adolescence: Evidence of amygdala hypersensitivity to signals of threat. (December 2015) - Spechler, Philip A.; Orr, Catherine A.; Chaarani, Bader; Kan, Kees-Jan; Mackey, Scott; Morton, Aaron; Snowe, Mitchell P.; Hudson, Kelsey E.; Althoff, Robert R.; Higgins, Stephen T.; Cattrell, Anna; Flor, Herta; et al.
Highlights: Teenagers experimenting with cannabis may be characterized with fMRI. We report a face processing study of cannabis experimenting teenagers. Cannabis experimenting teenagers exhibit greater amygdala reactivity to angry faces. Very low use of cannabis during adolescence may impact healthy emotional development. Abstract: Cannabis use in adolescence may be characterized by differences in the neural basis of affective processing. In this study, we used an fMRI affective face processing task to compare a large group ( n  = 70) of 14-year olds with a history of cannabis use to a group ( n  = 70) of never-using controls matched on numerous characteristics including IQ, SES, alcohol and cigarette use. The task contained short movies displaying angry and neutral faces. Results indicated that cannabis users had greater reactivity in the bilateral amygdalae to angry faces than neutral faces, an effect that was not observed in their abstinent peers. In contrast, activity levels in the cannabis users in cortical areas including the right temporal-parietal junction and bilateral dorsolateral prefrontal cortex did not discriminate between the two face conditions, but did differ in controls. Results did not change after excluding subjects with any psychiatric symptomology. Given the high density of cannabinoid receptors in the amygdala, our findings suggest cannabis use in early adolescence is associated with hypersensitivity to signals of threat. Hypersensitivity to negative affect in adolescence may place the subject at-risk for mood disorders in adulthood.